SOCS1 and SOCS3 are expressed in mononuclear cells in human cytomegalovirus viremia after allogeneic hematopoietic stem cell transplantation - Shin, Seung-Hwan; Lee, Ji Yoon; Lee, Tae Hyang; Park, So-Hye; Yahng, Seung-Ah; Yoon, Jae-Ho; Lee, Sung-Eun; Cho, Byung-Sik; Lee, Dong-Gun; Kim, Yoo-Jin; Lee, Seok; Min, Chang-Ki; et al. (Blood research, 2015)
The expression of the SOCS genes in cytomegalovirus (CMV) viremia after hematopoietic stem cell transplantation (HSCT) remains largely unexplored. Using quantitative RT-PCR of mononuclear cells, we conducted pairwise comparison of SOCS1 and SOCS3 expression levels among a healthy donor group (N=55), a pre-HSCT group (N=17), and the recipient subgroup (N=107), which were divided according to the occurrence of CMV viremia and acute graft-versus-host disease (aGVHD). Compared to that in the healthy donor group, SOCS1 expression was higher in the CMV+ subgroup, especially in the CMV+GVHD- group, but decreased in the other subgroups. When compared to the expression in the pre-HSCT group, SOCS1 expression was significantly higher in the CMV+ subgroup, especially in the CMV+GVHD+ subgroup. Meanwhile, compared to that in the healthy donor group, SOCS3 expression was significantly lower in all other groups. The CMV-GVHD- subgroup showed significantly lower SOCS3 expression compared to the CMV+ subgroup, the CMV+GVHD+ subgroup, and the CMV+GVHD- subgroup. We report differential expression of SOCS genes according to CMV viremia with acute GVHD occurrence after HSCT, suggesting that regulation of SOCS expression is associated with CMV viremia.